ChemInform Abstract: Magnetic Properties of Nanostructured Spinel Ferrites. Issue 2 (January 2015) - Cruz‐Franco, Berenice; Gaudisson, Thomas; Ammar, Souad; Bolarin‐Miro, Ana Maria; Sanchez de Jesus, Felix; Mazaleyrat, Frederic; Nowak, Sophie; Vazquez‐Victorio, Gabriela; Ortega‐Zempoalteca, Raul; Valenzuela, Raul
Abstract Review: 40 refs.